A country lawn - Johnson, Winifred Mae (My University, 1905)
Introduction: The true art of landscape gardening lies in such disposition of roadways walks and buildings as shall most effectively develop all the natural beauties of the land under treatments without conflicting and to be in harmony with the uses to which such lands may be devoted for a home. The interests of the home and its conveniences must be kept in view, and must never be sacrificed for some picturesque effect however beautiful or striking it may be. In a country home on Kansas soil much may be done by even the poorest labors to brighten his door-yard, if only a little care and forethought be used in planning as well as in execution, and if our poorer neighbor can improve his lawn, what may we not expect for our prosperous farmer, who has more time and means at his command. At the rate of advancement in all lines, it almost becomes a necessity that on the whole these be an improvement of country lawns in our Kansas homes.
The farmer's front yard
Citation: Johnson, Winifred Mae. A country lawn. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Surveyor's Map; Landscape Gardening Unity; Theses; Manuscripts (documents)